A comparative view on the tax performance of developing countries: Regional patterns, non-tax revenue and governance - Maksym Ivanyna; Christian von Haldenwang (Kiel Institute for the World Economy (IfW), 2012)
Some countries fail to ensure that their citizens and businesses make an appropriate contribution to the financing of public tasks. But not all countries with a low tax ratio automatically fall into this cat-egory. This paper presents an approach to bridge the gap between probabilistic statements based on statistical analyses, and country-specific information. Rather than defining general across-the-board criteria, the approach accounts for different development levels and other influencing factors, such as regional patterns, non-tax revenue and governance. Findings on individual countries or groups of countries should put governments, donors and international organisations in a better position to decide on tax reform programmes and aid modalities.
Keywords: H20; H60; H27; 330; tax system; tax ratio; governance; developing countries; Steuersystem; Steuerpolitik; Governance-Ansatz; Entwicklungsstufe; Entwicklungsländer